JDBC Recipes A Problem-Solution Approach - Parsian, Mahmoud (Apress : Imprint: Apress, 2005)
JDBC Recipes provides easy-to-implement, usable solutions to problems in relational databases that use JDBC. You will be able to integrate these solutions into your web-based applications, such as Java servlets, JavaServer Pages, and Java server-side frameworks. This handy book allows you to cut and paste the solutions without any code changes. This book focuses on topics that have been ignored in most other JDBC books, such as database and result set metadata. It will help you develop database solutions, like adapters, connectors, and frameworks using Java/JDBC. The insightful solutions will enable you to handle all data types, including large binary objects. A unique feature of the book is that it presents JDBC solutions (result sets) in XML.